Pendampingan Bimbingan Kelompok Belajar Matematika Berbasis Pendekatan Matematika Realistik Pada Siswa Kelas V Sekolah Dasar di Desa Witurombaua - Bhoke, wilibaldus; Suka, Felista Ripo (Bakti Cendana, 2024)
The community service carried out in Witurombaua Village with one of the most important activities is the mentoring of mathematics tutoring for elementary school students. The tutoring assistance activities were carried out at the Romba Catholic Elementary School with a total number of students participating in the tutoring activities as many as 7 students. The tutoring program in elementary schools is based on the Realistic Mathematics Learning approach, with the aim of increasing students' motivation and interest in learning mathematics. Realistic mathematics learning is an approach that places students' realities and experiences as the starting point of learning. The methods used in tutoring activities are lecture and discussion methods. The lecture method is a method that provides an explanation of material directly to students, while the discussion method is a method carried out by asking students about students' understanding of the material that has been explained. The existence of tutoring assistance activities can increase student learning interest in Cartesian coordinate material. This is seen from the ability of students' responses in learning activities. The tutoring assistance program has been well implemented and has provided positive benefits and impacts for elementary school students in Witurambaua village.